Communicating Banking Cyber-security Measures, Customer Ethical Concerns, Experience, and Loyalty Intentions: A Developing Economy’s Perspective - Mgiba, Freddy Marilahimbilu; Mxotwa, Thozama (International Review of Management and Marketing, 2024)
AI technology-based banking services development has disrupted the way people participate in banking transactions. It has created easier and faster banking transaction possibilities with the use of electronic gadgets. However, ethical concerns about these applications have also been amplified together with the need for management communication of safety features and protocols for customer information protection, and redress when infringements occur. The study was an attempt to highlight how AI-enabled banking services safety communication affects customers’ ethical concerns and how the concerns shape their banking services value perception, attitude, and loyalty intentions. A conceptual framework based on the generic AI technology, ethical concerns, and loyalty intentions was used as a basis for this study. It attempted to test the link between management communication, ethical concerns, satisfaction/dissatisfaction, and customer loyalty to AI-based banking services in a developing economy context. The study used three theoretical grounding bases to empirically test the proposed hypotheses. The results analysis followed Structural equation modeling (SEM). The results confirmed the impact of management communication on customers’ ethical concerns of security, privacy, diversity, and discrimination, and the positive influence of privacy and security on satisfaction/dissatisfaction. However, the relationship between diversity and discrimination concerns with customer satisfaction was not confirmed. Lastly, customer satisfaction was proven to impact their loyalty intentions.